Sistem Monitoring Suhu Udara dan Kelembaban Udara di Ruangan Menggunakan Smartphone: Array - Hasibuan, Ade Zulkarnain; Asih, Munjiat Setiani; Faisal, Ilham (Universitas Harapan Medan, 2020)
Human ignorance of their surroundings sometimes makes their health disturbed. Many factors cause a person to become uncomfortable, even to the point of making their health decline. Factors that can make a person uncomfortable and disturbed in terms of health are air temperature and humidity which are not suitable for the human body. Therefore we need a tool that can provide information to users about air temperature and humidity in the room where they are located. The tool is made using Arduino nano and uses the DTH11 sensor as a sensor which is used to read air temperature and humidity. Then to transmit the sensor value, the HC05 bluetooth module is used in the circuit. The smartphone will receive information on air temperature and humidity in real time. In applications on smartphones, in addition to the values of air temperature and humidity, there is also a smile indicator that provides information on air temperature and humidity that is good for humans. With this tool, it can make it easier for users to find out information on air temperature and humidity in the room in which they are located.